Outer Membrane Vesicles (OMVs) of Gram-negative Bacteria: A Perspective Update - Jan, Arif Tasleem (Frontiers in Microbiology, 2017)
Outer Membrane Vesicles (OMVs) of Gram-negative bacteria are spherical membrane-enclosed entities of endocytic origin. Reported in the consortia of different bacterial species, production of OMVs into extracellular milieu seems essential for their survival. Enriched with bioactive proteins, toxins, and virulence factors, OMVs play a critical role in the bacteria-bacteria and bacteria-host interactions. Emergence of OMVs as distinct cellular entities helps bacteria in adaptating to diverse niches, in competing with other bacteria to protect members of producer species and more importantly play a crucial role in host-pathogen interaction. Composition of OMV, their ability to modulate host immune response, along with coordinated secretion of bacterial effector proteins, endows them with the armory, which can withstand hostile environments. Study of the OMV production under natural and diverse stress conditions has broadened the horizons, and also opened new frontiers in delineating the molecular machinery involved in disease pathogenesis. Playing diverse biological and pathophysiological functions, OMVs hold a great promise in enabling resurgence of bacterial diseases, in concomitance with the steep decline in the efficiency of antibiotics. Having multifaceted role, their emergence as a causative agent for a series of infectious diseases increases the probability for their exploitation in the development of effective diagnostic tools and as vaccines against diverse pathogenic species of Gram-negative origin.